2011
DOI: 10.1111/j.1365-313x.2011.04518.x
|View full text |Cite
|
Sign up to set email alerts
|

The RLK/Pelle family of kinases

Abstract: The RLK/Pelle class of proteins kinases is composed of over 600 members in Arabidopsis. Many of the proteins in this family are receptor-like kinases (RLK), while others have lost their extracellular domains and are found as cytoplasmic kinases. Proteins in this family that are RLKs have a variety of extracellular domains that drive function in a large number of processes, from cell wall interactions to disease resistance to developmental control. This review will briefly cover the major subclasses of RLK/Pell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
178
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 217 publications
(180 citation statements)
references
References 155 publications
2
178
0
Order By: Relevance
“…Two prevalent extracellular protein domains consist of either leucine-rich repeats (LRRs) or lysin motifs (LysMs), which might interact with peptides or with N-acetyl-D-glucosamine (GlcNAc)-containing compounds, respectively [1,2].…”
mentioning
confidence: 99%
“…Two prevalent extracellular protein domains consist of either leucine-rich repeats (LRRs) or lysin motifs (LysMs), which might interact with peptides or with N-acetyl-D-glucosamine (GlcNAc)-containing compounds, respectively [1,2].…”
mentioning
confidence: 99%
“…LRR-containing proteins from plants have diverse overall structures and functions. Several classes contain LRR-containing receptor-like kinases (LRR-RLKs) [1,16], LRR-containing receptor-like proteins (LRR-RLPs) [10], nucleotide binding site LRR (NBS-LRR) proteins [7,26] and PolyGalacturonase Inhibiting Proteins (PGIPs) [8,9,30]. They provide an early warning system for the presence of potential pathogens and activate protective immune signaling in plants [20,18,35].…”
Section: Resultsmentioning
confidence: 99%
“…We observed that the endogenously modified 12-amino-acid (aa) CLV3p triggered similar responses to flg22 (the conserved 22-aa peptide of bacterial flagellin) in mesophyll protoplasts (Asai et al 2002;Shan et al 2008;Lee et al 2011). This finding was unexpected because CLV3p is normally expressed, secreted, and processed by stem cells to control SAM maintenance via CLV1, CLV2, and other receptors (Kondo et al 2006;Jun et al 2008;Gish and Clark 2011;Matsubayashi 2011;Aichinger et al 2012 (Asai et al 2002;He et al 2006;Shan et al 2008;Boller and Felix 2009;Boudsocq et al 2010). Highly purified CLV3p synthesized by different sources displayed the same activities, ruling out the possibility of contamination.…”
Section: Clv3p-mediated Sam Immunitymentioning
confidence: 96%
“…Because CLV3p is specifically expressed and secreted from stem cells of the SAM (Kondo et al 2006;Jun et al 2008;Gish and Clark 2011;Matsubayashi 2011;Aichinger et al 2012), it is critical to examine CLV3p-FLS2 signaling in the SAM to evaluate its physiological relevance. Using quantitative reverse transcription -polymerase chain reaction (qRT-PCR) analysis with isolated SAM tissues, CLV3p clearly triggered two parallel signaling pathways in the SAM.…”
Section: Clv3p-mediated Sam Immunitymentioning
confidence: 99%
See 1 more Smart Citation